A demonstrator of an Ethernet based embedded network in space launchers. Issue 1 (July 2017) - Petit, Dorine; Georges, Jean-Philippe; Divoux, Thierry; Regnier, Bruno; Miramont, Philippe
Abstract: The relationships between the French Space Agency (CNES) and the CRAN laboratory are 10 years old. In this framework, the CRAN has studied how the Ethernet standardized network may advantageously replace the old MIL-STD-1553B communication bus which is embedded today in the European launchers. Some classical requirements had to be respected, but specific constraints of the spatial field have been also met. Theoretical studies were leaded, and it was expected by the CNES to validate the academic results through real experimentations on which the results should be confirmed. A demonstrator has been designed which has fulfilled its role, but has also induced new unexpected problematics.